Evaluasi Pembelajaran Bahasa Arab Terhadap Metode pembelajaran Maharatul Kalam di SMP Islam Al-Azhar NW Kayangan Batu Layar Lombok Barat - Syahrul Izomi; Husnan Husnan (Universitas Muhammadiyah Mataram, 2023)
This study aims to explain the importance of evaluation as a component of learning, especially in teaching and learning Arabic. Learning is a relatively permanent change in behavior and is the result of repeated practice. In the learning process there are two main activities, namely learning that must be carried out by students and teaching which is carried out by the teacher whose direction of these two activities is to achieve predetermined goals in the form of learning outcomes both cognitive, affective and psychomotor. Research methods, Here we used a qualitative approach (qualitative approach). which (aimed at obtaining information related to the evaluation of learning Arabic in junior high school of islam NW Kayangan, Data collection technique Data collection techniques are data that can be carried out by interviews, question and answer, observation (observation) paper (symbols) and a combination of the three. The research data sources consist of three types, namely data sources in the form of person, place, and paper. Person, namely the source of data in the form of oral answers through the interview process, : Arabic subject teachers, and students. Place is a data source from fixed and dynamic conditions, this data source is generated through observation or observation, for example observing the process of learning Arabic in class. Then paper is a source of data in the form of symbols containing letters, numbers, pictures or others, such as documents or data related to history, vision and mission of the madrasa, conditions of teachers and students, conditions of facilities and infrastructure. Keywords Evaluation, learning, models, techniques, qowaid method, test and non-test assessment techniques.